INNOVATIVE SOLUTIONS TO PROTEC T WORKERS FROM DANGEROUS GAS AND TOXIC SUBSTANCES IN HAZARDOUS INDUSTRY ENTERPRISES - Muradov , Sirojiddin Husan o‘g‘li; Egamov , Dilshodbek Shavkat o‘g‘li (Educational Research in Universal Sciences, 2023)
This article reflects the deficiencies in some directions in the field of labor protection and technical safety and the recommendations for creating modern technologies and their practical application, relying on new innovative ideas to eliminate these deficiencies.